Acrotomopus atropunctellus (Coleoptera: Curculionidae) preference for large sugarcane shoots mitigates damage to sugarcane crop - Perez, Maria Lucia del Pilar; Isas, Marcos Gerardo; Salvatore, Analia Ruth; García, José María; Trumper, Eduardo Victor (BioOne, 2019)
The sugarcane weevil, Acrotomopus atropunctellus (Boheman) (Coleoptera: Curculionidae) is an increasingly important sugarcane pest in Argentina. Its emergence period overlaps with early stages of sugarcane phenology. This research assessed the preference of A. atropunctellus for shoot size and the effect of damage on shoot survival. Acrotomopus atropunctellus preferred to feed on large- and mediumsized shoots, regardless of sex. However, older plants were resistant to injury. Also, the number of punctures produced by females was 1.6 times greater than that produced by males. Avoiding late planting or harvest dates could be a useful tactic for mitigating A. atropunctellus incidence in sugarcane crops.